2020
DOI: 10.37236/9120
|View full text |Cite
|
Sign up to set email alerts
|

Extendable Shellability for $d$-Dimensional Complexes on $d+3$ Vertices

Abstract: We prove that for all $d \geq 1$, a shellable $d$-dimensional complex with at most $d+3$ vertices is extendably shellable. The proof involves considering the structure of `exposed' edges in chordal graphs as well as a connection to linear quotients of quadratic monomial ideals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…This theorem, along with results from [9], imply that for these complexes the notions of vertex decomposable, shellable, shelling completable, and extendably shellable are all equivalent.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…This theorem, along with results from [9], imply that for these complexes the notions of vertex decomposable, shellable, shelling completable, and extendably shellable are all equivalent.…”
Section: Introductionmentioning
confidence: 78%
“…In [9] it is shown that a d-dimensional complex ∆ on d + 3 vertices is extendably shellable if and only if ∆ is shellable. In this section we show that these conditions are also equivalent to ∆ being vertex decomposable.…”
Section: Complexes With Few Verticesmentioning
confidence: 99%
See 1 more Smart Citation